2010
DOI: 10.1016/j.jelectrocard.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The utility of modified Butler-Leggett criteria for right ventricular hypertrophy in detection of clinically significant shunt ratio in ostium secundum–type atrial septal defect in adults

Abstract: Our results indicate that there is limited utility of the BL criterion at detecting right ventricular volume overload, although a BL criterion value greater than 0 mV being used to identify patients with significant intracardiac shunts yielded a sensitivity of 0.68 and specificity of 0.65.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Siddiqui et al . reported that a Butler–Leggett criterion (calculated with QRS in I, V 1 , V 2 , and V 6 ) >0 mV may be used to identify patients with significant intracardiac shunts, with a sensitivity of 0.68 and a specificity of 0.65 . Moreover, Heller et al .…”
Section: Discussionmentioning
confidence: 99%
“…Siddiqui et al . reported that a Butler–Leggett criterion (calculated with QRS in I, V 1 , V 2 , and V 6 ) >0 mV may be used to identify patients with significant intracardiac shunts, with a sensitivity of 0.68 and a specificity of 0.65 . Moreover, Heller et al .…”
Section: Discussionmentioning
confidence: 99%
“…An independent observer (G.W.) confirmed the general accuracy of the automated QRS axis measurements by visually estimating the QRS axis using the amplitudes of the waveforms of the QRS complex 9 …”
Section: Methodsmentioning
confidence: 86%
“…7 With only the right ventricular volume overload produced by the so-called "ostium secundum" atrial septal defect, however, there is well-documented absence of right axis deviation. 8,9 Only the patients with defects permitting ventricular shunting, therefore, would be expected to have the increase in right ventricular wall tension that would affect its ventricular gradient sufficiently to alter both its depolarisation and repolarisation. The resultant late rightward QRS forces could be expected to "overbalance" the late leftward QRS forces caused by the abnormally positioned papillary muscles supporting the left atrioventricular valve.…”
mentioning
confidence: 99%
“…This modification is in accordance with methods used in a recent study by Siddiqui et al, in which the BL criteria were used in patients with RV volume overload. [13] The exclusion of R wave amplitudes in leads I or V 6 is valid as analysis of the formation of the ECG has shown that these waveforms do not reflect postero–lateral forces; this revision of the original BL methodology has been included in subsequent reprints of the formula. [14]…”
Section: Discussionmentioning
confidence: 99%
“…This modi ication is in accordance with methods used in a recent study by Siddiqui et al, in which the BL criteria were used in patients with RV volume overload. [13] The exclusion of R wave amplitudes in leads I or V 6 is valid as analysis of the formation of the ECG has shown that these waveforms do not re lect postero-lateral forces; this revision of the original BL methodology has been included in subsequent reprints of the formula. [14] The BL score used in the current study also differs from the VCG method used by Henkens et al [6] That method incorporates information regarding both ventricular depolarization and repolarization by analyzing both QRS complexes and T waves.…”
Section: Discussionmentioning
confidence: 99%